Hemostatic procedures in splenic trauma - Campos-Pérez, Ricardo; Parodi-Esteva, Hernán; Bianchi, Gerardo; Fernández Naone, Gonzalo; Mauro, Carlos; Bonaba, Roberto (Cirugía del Uruguay, 1983)
In new lesiona! models, severa! hemostatic procedures: electrocoagulation, simple individual arterial hemostasis, ischemic parenquimal suture and partialesplenectomy, are compared. In front of the lesiona! models and based in the experimental knowledge adquired, they conclude that ischemic parenquimal suture is the main procedure.